The Risk for Loneliness and Major Depression among Solo Agers. (May 2023) - Adams, Kathryn Betts; Parekh, Rupal; Mauldin, Rebecca L.; Fortinsky, Richard H.; Steffens, David C.
Solo agers may be vulnerable to social isolation and mental health sequelae, particularly if they lack close family or friendship ties. This study examined associations among indicators of solo aging, frequency of loneliness, and Major Depressive Disorder among adults aged 60+. Depressed participants were diagnosed by a geriatric psychiatrist and control participants were not depressed. We hypothesized that older adults with more indicators of solo aging (i.e., living alone, being unmarried, not having family or friends nearby) would be more often lonely and more likely to be depressed. In multivariate analyses controlling for health comorbidities and financial difficulty, each additional solo aging indicator significantly increased the likelihood of frequent loneliness, 95% CI OR [1.50, 2.80], and having a depression diagnosis 95% CI OR [1.04, 2.07]. Solo agers may be vulnerable to loneliness and depression, reinforcing the need for assessment and intervention for social isolation among older adults.